Ethnosciences learning related to socioscientific issues: Problems asked, science answered - Tsaniyah, Salma Putri; Fadly, Wirawan (Universitas Islam Negeri Raden Intan Lampung, 2024)
Ethnoscience learning incorporates local cultural aspects into science education, allowing students to engage with their environment and tackle real-world challenges. This study aims to examine the impact of ethnoscience learning on socioscientific issues in enhancing student engagement and environmental problem-solving skills at SMP Ma'arif 1 Ponorogo. A mixed-method experimental design was used, with quantitative data from pretest and posttest assessments and qualitative data from student observations. The findings indicate a significant improvement in student engagement and problem-solving abilities, as reflected in higher posttest scores and active participation. Thus, ethnoscience-based learning has been proven effective in enhancing scientific literacy and ecological awareness while also providing a contextual, meaningful, and relevant learning experience for everyday life. The implications of this study suggest the potential integration of diverse cultural perspectives into science education, ensuring that students from various backgrounds have equal opportunities to develop critical thinking and problem-solving skills to address environmental and social issues.